INFLUENCE OF CAPILLARIES ON HEMATOLOGICAL PARAMETERS OF INFESTED GEESE - Єресько, В. І. (Scientific Progress & Innovations, 2017)
The article presents the results of studies on the influence of different types of capillaries: Capilaria obsignata and Capilaria anseris on hematological parameters of infested geese. For the first time in Poltava region we proved parasitizing species of C. obsignata in geese. It was found that this species was less pathogenic than C. anseris. Parasitism of water fowl species C. anseris led to a significant reduction of hemoglobin in their blood, number of erythrocytes, significant increase number of leukocytes and we set growth percentage of eosinophils, reduction of lymphocytes and pseudoeosinophils.